Adolescent Gender Identity, Sexual Orientation, and Cannabis Use: Potential Mediations by Internalizing Disorder Risk. (February 2021) - Buttazzoni, Adrian; Tariq, Ulaina; Thompson-Haile, Audra; Burkhalter, Robin; Cooke, Martin; Minaker, Leia
Background/Aims: Adolescents who identify as nonbinary gender or as not heterosexual report higher levels of mental illness than their counterparts. Cannabis use is a commonly employed strategy to cope with mental illness symptoms among adolescents; however, cannabis use can have many deleterious health consequences for youth. Within the frame of minority stress theory, this study investigates the relationships between gender identity and sexual orientation, internalizing disorder symptoms, and cannabis use among adolescents. Method: A national cross-sectional survey of a generalizable sample of high school students in Canada from the 2017 wave ( N = 15, 191) of the Cancer Risk Assessment in Youth Survey was analyzed in spring 2019. Mediation analyses were completed to examine risk of internalizing disorder symptoms as a potential mediator of the association between (1) gender identity and (2) sexual orientation, and cannabis use. Results: Indirect effects in all models show significantly higher levels of reported internalizing disorder symptoms for female (OR = 3.44, 95% CI [2.84, 4.18]) and nonbinary gender (OR = 3.75, 95% CI [2.16, 6.51]) compared with male students. Sexual minority adolescents had higher odds of internalizing disorder risk relative to non–sexual minority adolescents (OR = 3.13, 95% CI [2.63, 3.74]). Students who reported higher rates of internalizing disorder symptoms were more likely to have ever used cannabis. Patterns of partial mediation are also present among all groups. Discussion/Conclusions: Findings can be used to better inform mental health interventions for adolescents. Future study should explore specific mental health stressors of vulnerable adolescent groups with respect to cannabis use as a coping mechanism.